Cost-Benefit Assessment of Climate and Weather Optimized Trajectories for Different North Atlantic Weather Patterns - Lührs, Benjamin; Niklaß, Malte; Frömming, Christine; Grewe, Volker; Gollnick, Volker (2018)
Besides CO2, the climate impact of commercial aviation is strongly influenced by non-CO2 effects, which are highly sensitive to meteorological conditions and their spatial variations. To assess the cost-benefit potential (climate impact mitigation vs. cost increase) of climate and weather optimized flight trajectories in the North Atlantic flight corridor, optimal control techniques are applied. However, the execution of multi-criteria route optimizations for an intercontinental route network and various weather patterns is computationally highly intensive. Since computational resources are limited, a reduced surrogate route network is generated and evaluated first with regard to the computational effort, the coverage in terms of available seat kilometers, as well as the accuracy of reproducing the original route network with regard to climate impact. The proposed reduced route network consists of 40 routes (original network: 1,359) and is able to reproduce the climate impact of the original route network with reasonable climate impact deviations of 2.5%. The evaluation of climate and weather optimized trajectories is performed for the top route of the surrogate network. The maximum climate impact reduction potential is differing strongly from 9% up to 60% for varying North Atlantic weather patterns. Averaged over the weather patterns, a maximum climate impact mitigation potential of about 32%, going along with a cost increase of about 8% has been estimated. However, at a cost penalty of 1%, a potential climate impact reduction of 24% has been observed.